Disentangling "worldview" in Religion & Worldviews education - Plater, Mark (Journal of Religious Education, 2025)
This paper addresses the conceptual confusion surrounding the term "worldview" in the context of England's proposed shift from traditional Religious Education to Religion and Worldviews education, as recommended by the Religious Education Council's Commission on Religious Education (CoRE) report (CoRE, Final report: Religion and Worldviews: The way forward, RE Council of England & Wales, 2018). The analysis reveals significant ambiguity in how "worldview" is applied to both personal existential experiences and organized community belief systems, creating pedagogical and theoretical challenges. Through examination of key documents from the REC Worldview Project and related scholarly responses, the paper demonstrates persistent definitional inconsistencies that undermine the clarity needed for effective classroom implementation. Conflating personal and institutional worldviews obscures important distinctions between individual meaning-making processes and collective religious or cultural frameworks. The paper proposes an alternative framework that reserves "worldview" exclusively for individual, lived experiences while introducing "community shared perspectives" for organized belief systems. This distinction recognizes that institutions provide agreed stories and practices but cannot themselves inhabit worldviews - only individuals can do so through their personal engagement with reality. The proposed model structures Religion and Worldviews education around three interconnected dimensions: personal worldviews (individual lived experience), communities of alignment (social groups sharing perspectives), and interpretive frameworks (belief systems and truth claims). This approach acknowledges the dynamic interplay between individual meaning-making, community belonging, and ideological influences while maintaining conceptual clarity. The framework positions Religion and Worldviews education as fundamentally concerned with exploring the human condition - addressing young people's needs for both belonging and meaning in an increasingly fragmented society. By providing clearer definitions and a more coherent pedagogical construct, this approach offers practical guidance for educators while honouring the complexity of religious and non-religious perspectives in contemporary multicultural contexts.